2013
DOI: 10.1017/s0033291713001669
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders in 22q11.2 deletion syndrome are prevalent but undertreated

Abstract: Background Chromosome 22q11.2 deletion syndrome (22q11DS) is a common genetic disorder with high rates of psychosis and other psychopathologies, but few studies discuss treatment. Our aim was to characterize the prevalence and treatment of major psychiatric illnesses in a well-characterized sample of individuals with 22q11DS. Method This was a cross-sectional study of 112 individuals aged 8 to 45 years with a confirmed diagnosis of 22q11DS. Each participant was administered a modified Schedule for Affective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 32 publications
(69 reference statements)
6
93
1
1
Order By: Relevance
“…Twenty-two of them (24.7%) fully met UHR criteria (i.e., including frequency and onset/ worsening requirements). Both rates are broadly consistent with previous studies in 22q11DS, reporting rates between 45 and 56% for UHR symptoms and between 10 and 21% for UHR criteria 10,11,[16][17][18]33 . Thus, our findings confirm that patients with 22q11DS are at increased risk of experiencing attenuated symptoms of psychosis, regardless of transition to psychosis 23,34 .…”
Section: Uhr Symptoms and Criteriasupporting
confidence: 91%
See 2 more Smart Citations
“…Twenty-two of them (24.7%) fully met UHR criteria (i.e., including frequency and onset/ worsening requirements). Both rates are broadly consistent with previous studies in 22q11DS, reporting rates between 45 and 56% for UHR symptoms and between 10 and 21% for UHR criteria 10,11,[16][17][18]33 . Thus, our findings confirm that patients with 22q11DS are at increased risk of experiencing attenuated symptoms of psychosis, regardless of transition to psychosis 23,34 .…”
Section: Uhr Symptoms and Criteriasupporting
confidence: 91%
“…Moreover, 22q11DS was found in 0.3 to 2.0% of patients with schizophrenia [12][13][14] , with rates of up to 5.7% in patients with childhood-onset schizophrenia 15 . Taken together, these findings indicate that 22q11DS is a highly relevant genetic risk factor for schizophrenia and the most promising human model for studying risk factors and states at risk for schizophrenia 5 .Several studies have investigated prodromal symptoms in patients with 22q11DS, reporting rates between 45 and 56% for UHR symptoms and between 10 and 21% for UHR criteria (including frequency and onset/worsening requirements) 8,10,11,[16][17][18] . Armando et al 8 compared the symptom profile of UHR patients with (N530) vs. without (N581) 22q11DS and found no significant group difference in positive symptoms, while negative symptoms were more severe in patients with 22q11DS.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Stigma was also experienced in relation to psychiatric illness, as 22q11DS patients are at higher risk for developing psychiatric illnesses, such as mood disorders, psychosis, or schizophrenia (Tang et al, 2014). The studies report that stigma experienced in relation to mental health, did not only appear to affect societal perceptions but also the possibility of parents unconsciously treating their child differently.…”
Section: Resultsmentioning
confidence: 99%
“…Its behavioural phenotype, including the psychopathological features and endocrine dysfunctions, especially hypoparathyroidism, was originally described by the speech therapist Robert Shprintzen [50]. Over subsequent years it became apparent that 22q11DS is highly associated with symptoms from the schizophrenia, bipolar, anxiety and autistic spectrum [51,52]. With respect to the neuropsychological phenotype, it has been shown that deficits in problem solving and planning as well as in abstract and social thinking are most prominent [53].…”
Section: Psychopathological Phenotypes: Some Examples 22q112 Microdementioning
confidence: 99%